The Global TanDEM-X DEM - A Unique Data Set - Zink, Manfred; Moreira, Alberto; Bachmann, Markus; Rizzoli, Paola; Fritz, Thomas; Hajnsek, Irena; Krieger, Gerhard; Wessel, Birgit (IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2017)
TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurements) is an Earth observation radar mission that consists of a SAR interferometer built by two almost identical satellites flying in close formation [1]-[4]. With a typical separation between the satellites of 120 to 500 m a global Digital Elevation Model (DEM) with 2 m relative height accuracy at 12 m posting has been generated. While the main mission phase for DEM data acquisition has been finished in 2014, the processing of the global TanDEM-X DEM was concluded in September 2016. Final DEMs are well within specifications and feature an extremely low percentage of void areas. Following the DEM data acquisition the capabilities of this unique mission for new scientific application have been demonstrated. Satellite resources allow for a continuation of the joint TerraSAR-X/TanDEM-X mission for several years. Beyond improvements of the global DEM the mission will be dedicated to the generation of a global 3D information change layer and of the corresponding DEM updates as a demonstration of the future climate research and environmental monitoring mission Tandem-L.
DLR Import::2019-04-03
Keywords: bistatic SAR formation; DEM updates; global Digital Elevation Model (DEM); SAR interferometry; TanDEM-X